Functional and Aesthetic Outcomes of Extracorporeal Septoplasty: A Systematic Review and Meta-Analyses. (April 2020) - Bresler, Amishav; Povolotskiy, Roman; Nguyen, Brandon; Zuliani, Giancarlo F.; Eloy, Jean Anderson; Paskhover, Boris; Svider, Peter
Objective: The safety and efficacy of extracorporeal septoplasty (ECS) has long been debated. Our objective was to determine this technique's functional and aesthetic outcomes and complications through a systematic review of the literature. Data Sources: PubMed/MEDLINE, Embase, Cochrane Library, and Web of Science databases were evaluated for studies detailing functional or aesthetic outcomes of ECS. Review Methods: Bias was evaluated using the Cochrane Risk of Bias Tool and the Methodological Index for Non-randomized Studies (MINORS) score. Aesthetic and functional outcomes in addition to complications were evaluated using subjective and objective measures. Meta-analyses were performed when appropriate. Results: Seventeen studies encompassing 1418 patients were included. The average MINORS score for observational studies was 9.2. Overall there was a significant improvement in subjective nasal function with a preoperative average Nasal Obstruction Symptom Evaluation (NOSE) score of 75 (±16) decreasing to 19.5 (±16.5) postoperatively for a mean difference (MD) of −55 (95% confidence interval (CI): –60 to −49.5). In terms of objective nasal function, at 6 months postoperatively, there was an improvement of nasal flow measured by rhinometry ranging from 70 to 71% across studies. Anthropometric measurements were utilized for objective aesthetic outcomes. There was a significant improvement in I-shaped deviations (MD: –2.7°, 95% CI: –5.6 to −0.16) and C-shaped deviations improved by 11.9° (95% CI +2.8-+21.2). Complication rates ranged from 0 to 18%. Conclusion: ECS can achieve significant improvements in the subjective and objective function of the nose. The associated complication rate is low but variable between surgeons.